Green Synthesis of Silver Nanoparticles Using Basilicum polystachyon Leaf Extract and Their Antibacterial Activity Against Staphylococcus aureus - Diyah Lailatul Agustin; Suyatno Sutoyo; Radita Yuniar Arizandy; Wahyu Setyarini (Helium: Journal of Science and Applied Chemistry, 2026)
AgNPs are nanomaterials with significant potential as antibacterial agents and can be synthesized in an environmentally friendly manner using plant extracts. This study aims to synthesize AgNPs using B. polystachyon leaf extract as a bioreductant and evaluate their antibacterial activity against S. aureus. The synthesis was performed by mixing B. polystachyon leaf extract with a 0.01 M AgNO₃ at volume ratios of 1:1, 1:2, 1:3, and 1:4, followed by pH optimization in the range of pH 8–11. The synthesized AgNPs were characterized using UV–Vis spectrophotometry, FTIR spectroscopy, PSA, and XRD. Antibacterial activity was evaluated using the disk diffusion method. The results showed that optimal synthesis conditions were achieved at a volume ratio of 1:4 and a pH of 11. The UV–Vis spectrum of the synthesized AgNPs exhibited a maximum absorption peak at 412 nm. FTIR analysis revealed the presence of O–H, aromatic C=C, and C–O bonds. The average particle size was 58.79 nm (PDI = 0.29). The XRD pattern confirmed the formation of crystalline silver.  The AgNPs inhibited the growth of S. aureus, with an inhibition zone diameter of 26.51 mm (very strong). Therefore, the synthesized AgNPs have the potential to be developed as antibacterial agents.